2005
DOI: 10.1097/01.ccm.0000186898.58709.aa
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tracheotomy on sedative administration, sedation level, and comfort of mechanically ventilated intensive care unit patients*

Abstract: On the basis of these observations, we conclude that tracheotomized mechanically ventilated ICU patients required less intravenous sedative administration, spent less time heavily sedated, and achieved more autonomy earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
160
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(178 citation statements)
references
References 34 publications
4
160
0
7
Order By: Relevance
“…Sedation requirements were not different between the two study groups, which is in part in line with recent data from our group [5] but opposite to results from others [6]. Unfortunately, however, data on cumulative dose were not given.…”
supporting
confidence: 71%
“…Sedation requirements were not different between the two study groups, which is in part in line with recent data from our group [5] but opposite to results from others [6]. Unfortunately, however, data on cumulative dose were not given.…”
supporting
confidence: 71%
“…However, no data exist that give adequate direction as to when it is routinely advisable to change from a translaryngeal intubation to a tracheostomy." 39 A recent comprehensive review of the Project IMPACT database (109 ICUs) documented that tracheostomy placement occurred at a median of 9 d (interquartile range [5][6][7][8][9][10][11][12][13][14] after ICU admission. In a secondary analysis comparing surgical ICU subjects (n ϭ 539) at Barnes-Jewish Hospital with subjects from 18 surgical ICUs in the Project IMPACT database, it was found that tracheostomy placement occurred more commonly in the Barnes-Jewish group (54.2% vs 13.9%, P Ͻ .001).…”
Section: Timing Of Tracheostomymentioning
confidence: 99%
“…3 Placement of a tracheostomy has become a viable alternative to prolonged endotracheal intubation, with the benefits of improving patient comfort, reducing need for sedation, lowering airway resistance, and allowing for easier airway care. [4][5][6] Complications related to tracheostomies include pneumothorax, bleeding, subglottic stenosis, tracheoesophageal fistula, vocal cord dysfunction, stomal granulation, persistent tracheal fistula, and scarring. 7 The indications, technique, timing, and selection of critically ill patients for tracheostomy have been topics of considerable debate.…”
Section: Introductionmentioning
confidence: 99%
“…Bu komplikasyonların riski translarengeal entübasyon süresi uzadıkça artmaktadır. Trakeostominin tüp bakımının daha kolay olması, sekresyon kontrolü, özellikli kanüller sayesinde hastanın iletişi-mine izin vermesi, oral beslenmeye olanak sağlaması, hemşire bakımının daha kolay ve daha güvenli olması gibi birçok potansiyel faydaları mevcuttur (7)(8)(9). Ayrıca translarengeal tüpe göre havayolu direncini azaltır, MV'den ayrılma sürecini hızlandırır, hastanede ve YBÜ'de kalış süresini kısaltır.…”
Section: Introductionunclassified